The Pengaruh Latihan Skipping Terhadap Daya Ledak Otot Tungkai Siswa Ekstrakurikuler Bulutangkis di MAN Sidoarjo - Haikal, Ahmad Fikri (Asosiasi Program Studi Olahraga PGRI Indonesia (APOPI), 2023)
This research uses a quantitative research approach. The focus of this research is the effect of skipping training on muscle explosive force and the influence of muscle explosive force on the jump smash of badminton extracurricular students at MAN Sidoarjo. Researchers obtained research data from several research samples in the game of badminton. Where the sample from this research was 15 extracurricular badminton students at MAN Sidoarjo. The research process lasted for 4 weeks, where in 1 week there were 2 meetings. The results of this study show that there is an increase in the explosive force of the leg muscles of badminton extracurricular students at MAN Sidoarjo. This is shown through the results of the analysis using SPSS 25, where the t-test results with a sig value were found. (2tailed) 0.003<0.05. The results of data analysis show that the t count is 2.878 and the t-table is 2.055 so that H0 is rejected and H1 is accepted, which means that skipping training can increase the explosive force of the leg muscles and maximize students' jump smashes.